2011
DOI: 10.1371/journal.pone.0016031
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Volumetric MRI Response Assessment of Enhancing Brain Tumors

Abstract: Current radiographic response criteria for brain tumors have difficulty describing changes surrounding postoperative resection cavities. Volumetric techniques may offer improved assessment, however usually are time-consuming, subjective and require expert opinion and specialized magnetic resonance imaging (MRI) sequences. We describe the application of a novel volumetric software algorithm that is nearly fully automated and uses standard T1 pre- and post-contrast MRI sequences. T1-weighted pre- and post-contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 41 publications
0
47
1
Order By: Relevance
“…Other studies have described similar computer-aided techniques in the evaluation of gliomas; however, validation against other measurement techniques is lacking. 15 Bidimensional techniques used in the MacDonald and RANO criteria are currently the most commonly used techniques for GBM assessment; however, studies have reported high interobserver and intraobserver variability, even among individuals with specialty training in neuroradiology. 24,25 The increased variability in diameter-based approaches likely stems from the inherent irregularities in GBM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have described similar computer-aided techniques in the evaluation of gliomas; however, validation against other measurement techniques is lacking. 15 Bidimensional techniques used in the MacDonald and RANO criteria are currently the most commonly used techniques for GBM assessment; however, studies have reported high interobserver and intraobserver variability, even among individuals with specialty training in neuroradiology. 24,25 The increased variability in diameter-based approaches likely stems from the inherent irregularities in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…14 Application of computer-assisted volumetry (CAV) has been explored for the evaluation of gliomas; however, these studies have dealt with native nontreated disease and have not been validated against other measurement techniques. [15][16][17] In this study, we describe a novel CAV technique for assessment of tumor burden in the patient with GBM. Specifically, we describe the reliability and feasibility of this technique compared with traditional linear-based measurements in the patient with postresection GBM.…”
mentioning
confidence: 99%
“…Voxel-to-voxel image subtraction between T1-weighted images before and after contrast administration may detect subtle enhancement that can easily be interpreted as non-enhancement by visual analyses. The use of T1-subtraction maps may provide a more accurate assessment of true tumor extent in the context of antiangiogenic treatment [47•, 81,82].…”
Section: Evaluation Of Non-enhancing Tumor Burdenmentioning
confidence: 99%
“…This leads to the need for accurate brain magnetic resonance image (MRI) segmentation into gray matter (GM) [1], white matter (WM), cerebrospinal fluid (CSF), and also to define tumours or lesions if present [2,3].…”
Section: Introductionmentioning
confidence: 99%